Challenges and Strategies in Implementing Immunization Programs at a Primary Healthcare Center - Muhammad Yuyut Ariyanto; Sabran Sabran; Aini Aini (PT. Global Research Collaboration, 2026)
Immunization is one of the most effective public health interventions for preventing infectious diseases and reducing morbidity and mortality rates. In Indonesia, immunization policies have been regulated through various national health regulations. However, the implementation of these policies at the local level still faces several challenges. This study aims to identify the main barriers in the implementation of the immunization program and to explore effective strategies to improve immunization coverage at the Loa Janan Community Health Center (Puskesmas), Kutai Kartanegara Regency. This research employed a mixed-method approach combining qualitative and quantitative techniques. Data were collected through in-depth interviews with health workers and community members, surveys distributed to parents of eligible children, and field observations of immunization service delivery. The findings indicate that although the immunization program at the Loa Janan Health Center has generally been implemented effectively, several obstacles remain. These include limited community awareness regarding the importance of immunization, geographical barriers that affect service accessibility, and the dissemination of health information that has not yet reached all segments of the community effectively. To address these challenges, several efforts have been implemented, including community education and socialization programs, cross-sectoral collaboration with local stakeholders, and service innovations aimed at improving accessibility and community engagement. The results of this study provide practical insights and policy recommendations that can support the improvement of immunization programs and strengthen public health policy implementation at the local level.